Superconductive bolometers and calorimeters - Kraus, H (1996)
Superconducting bolometers and calorimeters are used in many applications, such as infrared astronomy, fast spectroscopy of condensed matter excitations or even in particle physics and plasma diagnostics. The development in this field has a long history and is very active and numerous successful applications can be counted. Many of the detectors discussed in this article make use of the steepness of the resistance-temperature characteristics at the transition between the normal and superconducting phase of superconductors. This overview includes low-TC calorimeters, mainly for applications to particle and astrophysics, and high-TC bolometers which could replace presently used detectors. In addition, related detection techniques will be addressed.